Knowledge insufficient: the management of haemoglobin SC disease. (16th December 2016) - Pecker, Lydia H.; Schaefer, Beverly A.; Luchtman‐Jones, Lori
Summary: Although haemoglobin SC (HbSC) accounts for 30% of sickle cell disease (SCD) in the United States and United Kingdom, evidence‐based guidelines for genotype specific management are lacking. The unique pathology of HbSC disease is complex, characterized by erythrocyte dehydration, intracellular sickling and increased blood viscosity. The evaluation and treatment of patients with HbSC is largely inferred from studies of SCD consisting mostly of haemoglobin SS (HbSS) patients. These studies are underpowered to allow definitive conclusions about HbSC. We review the pathophysiology of HbSC disease, including known and potential differences between HbSS and HbSC, and highlight knowledge gaps in HbSC disease management. Clinical and translational research is needed to develop targeted treatments and to validate management recommendations for efficacy, safety and impact on quality of life for people with HbSC.